Genetic disruption of the KLF1 gene to overexpress the γ‐globin gene using the CRISPR/Cas9 system. (October 2016) - Shariati, Laleh; Khanahmad, Hossein; Salehi, Mansoor; Hejazi, Zahra; Rahimmanesh, Ilnaz; Tabatabaiefar, Mohammad Amin; Modarressi, Mohammad Hossein
Abstract: Background: β‐thalassemia comprises a major group of human genetic disorders involving a decrease in or an end to the normal synthesis of the β‐globin chains of hemoglobin. KLF1 is a key regulatory molecule involved in the γ‐ to β‐globin gene switching process directly inducing the expression of the β‐globin gene and indirectly repressing γ‐globin. The present study aimed to investigate the ability of an engineered CRISPR/ Cas9 system with respect to disrupting the KLF1 gene to inhibit the γ‐ to β‐hemoglobin switching process in K562 cells. Methods: We targeted three sites on the KLF1 gene, two of which are upstream of codon 288 in exon 2 and the other site being in exon 3. Results: The average indel percentage in the cells transfected with CRISPR a, b and c was approximately 24%. Relative quantification was performed for the assessment of γ‐globin expression. The levels of γ‐globin mRNA on day 5 of differentiation were 8.1‐, 7.7‐ and 1.8‐fold in the cells treated with CRISPR/ Cas9 a, b and c, respectively, compared to untreated cells. The measurement of HbF expression levels confirmed the same results. Conclusions: The findings obtained in the present study support the induction of an indel mutation in the KLF1 gene leading to a null allele. As a result, the effect of KLF1 on the expression of BCL11A is decreased and its inhibitory effect on γ‐globin gene expression is removed. Application of CRISPR technology to induce an indel in the KLF1 gene in adult erythroid progenitors may provide a method for activating fetal hemoglobin expression in individuals with β‐thalassemia or sickle cell disease.